PEMANFAATAN INTERNET OF THINGS PADA KENDALI LAMPU - Anggraini Kusumaningrum; Asih Pujiastuti; Muhammad Zeny (Compiler, 2017)
Lamp is a kind of electronic that created light. Light is obtained through the flow of electricity as a current to add a voltage. the die and the life of light are controled  by humans using switch. Applying the  Internet of Things, as known as IoT determined the life and the die of a lamp by determined by the active light censor. The die and the life of the lamp automatically depends on the light sensor by capturing the intensity of the light produced. The result of the function test found that the data in the form of lux value generated by the light sensor, the value is exposed on a website with the display of graphics and websites serve as a web service provides control values to determine the response lamp, if the value of lux above 30 percent then the lights off And vice versa if under 30 percent of the lamps are on, so that a small value will be sent to the lamp and the lamp will respond that the lights are off or on. So that humans only act as a watchdog and control of the value generated by the light sensor.